2014
DOI: 10.1097/ccm.0000000000000545
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Influenza-Associated Critical Illness Hospitalizations*

Abstract: Objective Influenza is the most common vaccine-preventable disease in the United States; however, little is known about the burden of critical illness due to influenza virus infection. Our primary objective was to estimate the proportion of all critical illness hospitalizations that are attributable to seasonal influenza. Design Retrospective cohort study Setting Arizona, California, and Washington from January 2003 through March 2009 Patients All adults hospitalized with critical illness, defined by ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 37 publications
(44 reference statements)
1
54
0
4
Order By: Relevance
“…A similar regression‐based study by Ortiz et al20 found only 1 of 10 influenza‐associated critical illness hospitalizations included an influenza diagnosis (including clinical diagnoses of ILI), compared to our estimate of 1 of 3 for respiratory patients admitted to a special care unit. A US study by Zhou et al21 found similar patterns for influenza and RSV, noting that although the overall morbidity burden of influenza and RSV was similar, the age‐specific burdens differ dramatically.…”
Section: Discussionsupporting
confidence: 63%
“…A similar regression‐based study by Ortiz et al20 found only 1 of 10 influenza‐associated critical illness hospitalizations included an influenza diagnosis (including clinical diagnoses of ILI), compared to our estimate of 1 of 3 for respiratory patients admitted to a special care unit. A US study by Zhou et al21 found similar patterns for influenza and RSV, noting that although the overall morbidity burden of influenza and RSV was similar, the age‐specific burdens differ dramatically.…”
Section: Discussionsupporting
confidence: 63%
“…Ortiz and collaborators [32] Hospital 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) Limitation of therapy in-hospital, n (%) DNR 72 (11.9) WH/WD 57 (9.4) about 28,000 adults are hospitalized for influenza-associated critical illness in the USA annually. A recent biasadjusted meta-analysis [33] confirmed that influenza vaccine was effective in preventing hospitalization from influenza and/or pneumonia and all-cause mortality in community-dwelling elderly.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 28,000 of critical-illness hospitalizations are attributed annually to seasonal influenza17. The number of hospitalization increased to approximately 274,000 during 2009 H1N1 pandemic leading to more than 12,000 deaths in the USA only18.…”
Section: Resultsmentioning
confidence: 99%